The relationship between blood perfusion and thermal measurements at the skin surface - Nicholson, Christopher P. B. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2006)
Blood perfusion is defined as the volumetric flow rate of blood through a given volume of tissue. Blood perfusion measurements are an important clinical indicator for many medical conditions but to date there is no cost effective and accurate measurement solution available. Among a number of existing perfusion measurement techniques there is a range of thermal methods; these thermal methods offer the prospect of cheap and accurate perfusion measurement devices. The aim of this study is to investigate the relationship between non-invasive surface thermal measurements and the perfusion levels in the various tissues of the lower arm, leg and finger with a view to ultimately developing a practical, non-invasive and cost effective perfusion measurement device. The most promising thermal technique to date is known as the Forced Convection Approach in which a localised cooling load is applied to a small section of the skin surface using a perfusion probe. The thermal response at the surface is then related to the value of perfusion using a numerical model of the system based on an appropriate bio-heat model. Initial work repeating that of previous researchers identified a number of areas in which experimental and numerical improvements were required. A number of important developments were first made to the experimental procedure. A greater appreciation of the simplifying assumptions and applicability of the model was then developed. A crucial development was the concept of the Possible Perfusion Values curve; this refined approach was then implemented. A further simpler but novel technique, namely the Steady State Perfusion Measurement Technique was also developed based on the PPV methodology.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin